Buying Indonesian: How identity, trust, and perception shape support for local brands - Septiani, Emilia; Yasa, Ni Nyoman Kerti; Ekawati, Ni Wayan; Sukaatmadja, I Putu Gde (Edelweiss Applied Science and Technology, 2025)
In Indonesia’s rapidly expanding cosmetic market, local brands face the dual challenge of competing with global beauty giants while appealing to increasingly identity-conscious consumers. This study investigates the drivers of purchase intention toward local cosmetic brands by integrating the Theory of Planned Behavior (TPB), Social Identity Theory (SIT), and Categorical Cognition Theory (CCT). Using data from 250 young Indonesian consumers and structural equation modeling, the study examines how Home Country Image (HCI) and Consumer Ethnocentrism (CE) influence purchase intention through Brand Image (BI), Product Belief (PB), and Attitude (ATT). Results reveal that HCI and CE significantly shape BI, PB, and ATT, but their influence on purchase intention is only realized when consumers hold strong beliefs in product quality. Surprisingly, brand image does not directly affect intention, challenging conventional wisdom in cosmetic marketing. This study contributes a novel multidimensional framework for understanding local brand loyalty in emerging markets and offers actionable insights for enhancing trust, cultural relevance, and competitiveness in the Indonesian beauty industry.